2013
DOI: 10.1021/jm400963y
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of Novel Tetrahydropyran-Based Bacterial Topoisomerase Inhibitors with Potent Anti-Gram-Positive Activity

Abstract: There is an urgent need for new antibacterial drugs that are effective against infections caused by multidrug-resistant pathogens. Novel nonfluoroquinolone inhibitors of bacterial type II topoisomerases (DNA gyrase and topoisomerase IV) have the potential to become such drugs because they display potent antibacterial activity and exhibit no target-mediated cross-resistance with fluoroquinolones. Bacterial topoisomerase inhibitors that are built on a tetrahydropyran ring linked to a bicyclic aromatic moiety thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
108
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 45 publications
6
108
0
Order By: Relevance
“…Mechanistic studies with NBTIs have revealed that members of this class are similar to the fluoroquinolones in that they bind to the DNAbound form of gyrase and topoisomerase IV; however, structural studies have revealed a binding site distinct from that of fluoroquinolones (16,17). Our earlier effort in this series of compounds, as well as recent work from other investigators, was focused on optimizing potency and safety, with an emphasis on Gram-positive pathogens (18)(19)(20)(21)(22). The discovery of NBTI 5463, whose spectrum of activity includes P. aeruginosa and is not affected by the target-based point mutations associated with resistance to fluoroquinolones, represents an advance with this emerging class of agents.…”
mentioning
confidence: 99%
“…Mechanistic studies with NBTIs have revealed that members of this class are similar to the fluoroquinolones in that they bind to the DNAbound form of gyrase and topoisomerase IV; however, structural studies have revealed a binding site distinct from that of fluoroquinolones (16,17). Our earlier effort in this series of compounds, as well as recent work from other investigators, was focused on optimizing potency and safety, with an emphasis on Gram-positive pathogens (18)(19)(20)(21)(22). The discovery of NBTI 5463, whose spectrum of activity includes P. aeruginosa and is not affected by the target-based point mutations associated with resistance to fluoroquinolones, represents an advance with this emerging class of agents.…”
mentioning
confidence: 99%
“…In one study, for example, NBTI analogs displayed equipotent target affinity for Streptococcus pneumoniae gyrase and TopoIV but an asymmetrical profile toward the Staphylococcus aureus enzymes, with greater affinity for S. aureus gyrase (40). Another group concluded that an asymmetrical target profile in S. aureus led to unacceptably high resistance frequencies (3 ϫ 10 Ϫ6 at 4ϫ MIC) (41). This group directed compound optimization toward a balanced target profile in S. aureus and demonstrated that an analog with equipotent target affinities had a reduced spontaneous resistance mutation frequency (5 ϫ 10 Ϫ8 at 4ϫ MIC).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to fluoroquinolones, they bind near the catalytic center of DNA gyrase and topoisomerase IV but are structurally and mechanistically distinct from fluoroquinolones. Due to this differential action, they possess enhanced potency against Grampositive organisms, including methicillin-resistant Staphylococcus aureus (MRSA) as well as penicillin-and fluoroquinolone-resistant Streptococcus pneumoniae (1,(3)(4)(5).The goal of the present experiments was to assess the in vivo pharmacokinetics (PK)/pharmacodynamics (PD) characteristics of two topoisomerase inhibitors under development in the mouse thigh infection model against two target bacterial species, S. aureus and S. pneumoniae.(Part of this work was presented at the 55th Interscience Conference on Antimicrobial Agents and Chemotherapy, San Diego, CA, September 2015 [21,22]. )…”
mentioning
confidence: 99%
“…Similarly to fluoroquinolones, they bind near the catalytic center of DNA gyrase and topoisomerase IV but are structurally and mechanistically distinct from fluoroquinolones. Due to this differential action, they possess enhanced potency against Grampositive organisms, including methicillin-resistant Staphylococcus aureus (MRSA) as well as penicillin-and fluoroquinolone-resistant Streptococcus pneumoniae (1,(3)(4)(5).…”
mentioning
confidence: 99%